Antioxidative defence under drought stress in a wheat stay-green mutant - F. X. Tian; M. Zhang; X. Wang; Y. H. Chen; W. Wang (Biologia Plantarum, 2015)
A wheat stay-green mutant, named tasg1, was generated using the mutagen ethyl methane sulphonate applied to wheat (Triticum aestivum L.) cv. HS2. A drought stress was imposed by controlling irrigation and sheltering plants from rain. The antioxidant defence was characterized in the flag leaves of the tasg1 and wild-type (WT). Compared with WT, tasg1 had higher reduced ascorbate/oxidized ascorbate ratio, reduced glutathione/oxidized glutathione ratio, and antioxidant enzyme activities during senescence under both normal and drought stress conditions. The DHAR gene expression remained higher in tasg1 than in WT during the drought stress and tasg1 had a higher antioxidant defence competence which may contribute towards the delayed leaf senescence. The different transcriptional responses of some wheat senescence-associated genes to the drought stress between tasg1 and WT were observed. These results suggest that the competent antioxidative capacity might play an important role in the enhanced drought tolerance in tasg1.